The role of self-efficacy in women’s autonomy for health and nutrition decision-making in rural Bangladesh - Salinger, Allison; Vermes, Ellen; Waid, Jillian; Wendt, Amanda; Dupuis, Sarah J. N.; Kalam, Md Abul; Kader, Abdul; Sinharoy, Sheela S. (BMC public health, 2024)
Background: Agency – including the sub-domains of intrinsic agency, instrumental agency, and collective agency – is a critical component of the women’s empowerment process. Self-efficacy (a component of intrinsic agency) may operate as a motivational influence for women to make choices according to their own preferences or goals, such that higher self-efficacy would be associated with more autonomous decision-making (a key component of instrumental agency). Methods: We examine these relationships using mixed methods. We developed a series of decision-making autonomy indices, which captured alignment between the woman’s reported and preferred roles in health and nutrition decisions. Using ordinal logistic regression, we assessed the relationship between generalized self-efficacy and decision-making autonomy. Results: There was a consistently positive association across all categories of decision-making, controlling for a number of individual and household-level covariates. In a sub-sample of joint decision-makers (i.e., women who reported making decisions with at least one other household member), we compared the association between generalized self-efficacy (i.e., one’s overall belief in their ability to succeed) and decision-making autonomy to that of domain-specific self-efficacy (i.e., one’s belief in their ability to achieve a specific goal) and decision-making autonomy. Across all decision-making categories, domain-specific self-efficacy was more strongly associated with decision-making autonomy than generalized self-efficacy. In-depth interviews provided additional context for interpretation of the regression analyses. Conclusions: The results indicate the importance of the role of self-efficacy in the women’s empowerment process, even in the traditionally female-controlled areas of health and nutrition decision-making. The development of the decision-making autonomy index is an important contribution to the literature in that it directly recognizes and captures the role of women’s preferences regarding participation in decision-making.